2019
DOI: 10.1002/pbc.27903
|View full text |Cite
|
Sign up to set email alerts
|

Identifying patient‐centered outcomes for children with cancer and their caregivers when they seek care in the emergency department

Abstract: Background: Children with cancer have high utilization of the emergency department (ED), but little is known about which outcomes are most important to them and their caregivers when they seek care in the ED.Procedure: A qualitative evaluation of ED experience for children with cancer and their caregivers was performed using self-reported interactive toolkits. Eligible participants included children with cancer (ages 11-19) and caregivers of children with cancer whose child received cancer therapy within the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 34 publications
2
5
0
Order By: Relevance
“…In order to protect these children from further risk of infection (i.e., from crowded ED lobbies), and facilitate early assessment and rapid triage, specific protocols need to be in place to isolate and evaluate these patients in a timely manner. 27 Caregivers often avoid bringing their children into a crowded ED, unless they perceive severe illness or if instructed by their primary care provider or oncologist. For minor issues, such as muscular injuries, caregivers would seek care on an outpatient basis, as opposed to non-immunocompromised patients who would be more likely to visit the ED for non-acute and non-serious medical issues.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to protect these children from further risk of infection (i.e., from crowded ED lobbies), and facilitate early assessment and rapid triage, specific protocols need to be in place to isolate and evaluate these patients in a timely manner. 27 Caregivers often avoid bringing their children into a crowded ED, unless they perceive severe illness or if instructed by their primary care provider or oncologist. For minor issues, such as muscular injuries, caregivers would seek care on an outpatient basis, as opposed to non-immunocompromised patients who would be more likely to visit the ED for non-acute and non-serious medical issues.…”
Section: Discussionmentioning
confidence: 99%
“…However, ED visits have their own risks by exposing children to infectious agents that may have devastating consequences. In order to protect these children from further risk of infection (i.e., from crowded ED lobbies), and facilitate early assessment and rapid triage, specific protocols need to be in place to isolate and evaluate these patients in a timely manner 27 . Caregivers often avoid bringing their children into a crowded ED, unless they perceive severe illness or if instructed by their primary care provider or oncologist.…”
Section: Discussionmentioning
confidence: 99%
“…RJ has completed projects addressing various research challenges including identifying patient-centered outcomes [35,36], developing interventions [37,38], improving research study recruitment [39] and experience [40] to improve research outcomes, and communicating health information to the public [41].…”
Section: Type 1 Diabetes Mellitus (T1dm)mentioning
confidence: 99%
“…4,5 Based on our clinical experience and recent study, we appreciate that children with cancer and their caregivers encounter many barriers to optimal care when preparing for and then seeking care in the ED. 6 First, most newly-diagnosed pediatric cancer patients were previously healthy and unlikely to have experienced serious medical issues. Consequently, caregivers may be unfamiliar with navigating the healthcare system, especially when medical emergencies arise.…”
Section: Introductionmentioning
confidence: 99%
“…7,8,9 Our previous evaluation of important outcomes to children with cancer and their caregivers when they seek care in the ED revealed that they desired a way in which to improve their sense of preparedness. 6 One way in which we believed we could support caregivers in their need to feel more prepared for when medical emergencies arise is through a mobile health (mHealth) technology tool. A mHealth tool could enable caregivers to become more efficient, effective, safer, and less stressed while managing their childrens' care.…”
Section: Introductionmentioning
confidence: 99%